Hysteroscopic-guided removal of retained intrauterine device: Experience at an Academic Tertiary Hospital - Ma. Rosielyn D. Asto; Maria Antonia E. Habana (Wolters Kluwer Medknow Publications, 2018)
Background: Removal of an intrauterine device can be easily done when the string is visible during speculum exam. The task becomes challenging when the string is no longer visible. Methodology: The in-patient and out-patient medical records of all patients admitted for hysteroscopic-guided intrauterine device removal from January 2013 to December 2015 from a tertiary academic government hospital were retrieved and reviewed. Demographic data, intraoperative record, and post-operative course and outcome were obtained. Prior attempts on removal were also noted. Total operative time, type of IUD removed, operative findings and any complications encountered were recorded. The size and model of the hysteroscope were also noted. Results: Nineteen patients were included, twelve were of reproductive age and seven were already in their menopausal years. Majority were multigravida. Reasons for IUD removal for most patients were spotting, desire for pregnancy, and expired date of use. All patients had prior attempts of ultrasound guided IUD removal. Majority of patients had unremarkable post-operative course and no readmissions were noted. Conclusion: Hysteroscopic-guided removal of IUD is a superior option for management when ultrasound guided removal fails. Unnecessary major operation and complications were avoided. In the three - year experience, there has been no major complications and re-admissions related to the procedure. Hysteroscopic removal of IUD was shown to be an effective option after failed ultrasound-guided removal with low risk of complications.